Electrocardiographic Parameters in Iranian Children Referring to Hospitals Affiliated with Mashhad University of Medical Sciences - Feisal Rahimpour; Elahe Heidari; Nazanin Moavenzadeh Ghaznavi; Lida Jarahi; Mozhgan Mansoorian (Research in Cardiovascular Medicine)
Background: Various studies and guidelines have been published for the interpretation of electrocardiograms (ECGs) around the world. However, there is insufficient evidence supporting the relationship between race, ethnicity, and ECG parameters in the pediatric population. Objectives: This study is a pioneering effort to create a standardized registry in Iran, aiming to determine normal electrocardiographic parameters for Iranian children. Methodology: This preliminary pilot study was a descriptive cross-sectional type. Digital electrocardiography data (with 12 leads) of 382 boys and girls aged 1–216 months (18 years) who visited 3 children’s hospitals affiliated with Mashhad University of Medical Sciences were collected over 2 years. The main ECG values examined in this study included the P, QRS, T, U waves, PR interval, QT interval, QTc interval, heart rate (HR), and PR segment. For describing quantitative data, measures of central tendency such as mean and median, and measures of dispersion including standard deviation, range, and quartiles were used. For describing qualitative variables, the percentage of frequency was used. Quantitative data descriptions were done separately by gender and age groups. Results: HR and ECG parameters by sex and age group (1 month–18 years) were measured in this study. Conclusion: Our findings differ from those of previous studies. These differences might be due to the limitations of this study, such as the sample size and the diversity of racial backgrounds. To fully comprehend these discrepancies, it is important to establish registries and conduct studies with larger sample sizes.